Repolarization Dispersion Is Associated With Diastolic Electromechanical Discoordination in Children With Pulmonary Arterial Hypertension - Michal Schäfer; Benjamin S. Frank; D. Dunbar Ivy; Max B. Mitchell; Kathryn K. Collins; Pei‐Ni Jone; Johannes C. von Alvensleben (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Electromechanical dyssynchrony is a well described comorbidity in pulmonary arterial hypertension (PAH). ECG‐derived measurements reflective of diastolic dysfunction and electromechanical imaging markers are yet to be investigated. In this study we investigated the ECG‐ derived marker of repolarization dispersion, interval between the peak and end of T wave (TpTe), in pediatric patients with PAH and left ventricular (LV) diastolic dysfunction. Methods and Results We measured TpTe from a standard 12‐lead ECG and in 30 children with PAH and matched control subjects. All participants underwent same‐day echocardiography and myocardial strain analysis to calculate the diastolic electromechanical discoordination marker diastolic relaxation fraction. When compared with control subjects, patients with PAH had increased TpTe (93±15 versus 81±12 ms, P=0.001) and elevated diastolic relaxation fraction (0.33±0.10 versus 0.27±0.03, P=0.001). Patients with PAH with LV diastolic dysfunction had significantly increased TpTe when compared with patients with PAH without diastolic dysfunction (P=0.012) and when compared with control group (P<0.001). Similarly, patients with PAH with LV diastolic dysfunction had increased diastolic relaxation fraction when compared with PAH patients without diastolic dysfunction (P=0.007) and when compared with control group (P<0.001). A 10‐ms increase in TpTe was significantly associated with 0.023 increase in diastolic relaxation fraction (P=0.008) adjusting for body surface area, heart rate, right ventricular volumes, and function. Conclusions Prolonged myocardial repolarization and abnormal LV diastolic electromechanical discoordination exist in parallel in children with PAH and are associated with worse LV diastolic function and functional class.